Concept of fast dissolving formulations for use in acute treatment conditions â€“ introspection, thoughts and perspectives (Asian Journal of Pharmaceutics (AJP), 2014)
In a recent issue of AJP, Ranagasamy et al. (2009) haveprovided a succulent report on the development of afast dissolving tablet of terbutaline sulfate for possiblehuman use in the timely management of asthmaticepisodes.[1] The design and evaluation part of the worksuggested that careful consideration was taken from theselection of excipients until the dissolution testing ofthe tablets to confirm its intended utility.[1] However,an important missing link in this work was to confirmwhether or not such a system would work under invivo conditions to ensure rapid drug delivery has notbeen compromised. Hence, it need to be questionedand challenged when emphatic conclusion statingthat â€œthe new fast dissolving terbutaline formulationis better than the conventional tablet dosage formused in the management of asthmaâ€ has been madein the published work without adequate support toback it up.[1] While it is acknowledged that it may bedifficult for academic/research institutions or fledglingbiotechs to perform in vivo evaluations due to the lackof resources, trained personnel and/or funding issues,in some extraordinary cases it may be a good idea toexplore testing of the new formulation in a preclinicalmodel for getting clarity on the in vivo performance ofthe new formulation. Needless to say, the final utilityof the innovation and design of the new formulation issolely dependent on its in vivo performance.